(untitled) (Pakistan Journal of Kidney Diseases, 2026)
ABSTRACT: Malnutrition remains an under-recognized complication in peritoneal dialysis patients, driven by inadequate dietary intake. This study aimed to assess dietary protein and fiber intake in relation to their nutritional status among PD patients. Methods: A retrospective study was conducted using medical records of 56 PD patients followed at PD Clinic from 2024–2026. Dietary intake was assessed using documented 24-hour dietary recall records. Dietary protein, fiber, potassium, and phosphorus intake were assessed using USDA food composition values. Nutritional status was evaluated using serum albumin, BMI, and clinical records. Results: A significant positive correlation of dietary fiber was observed with dietary protein (p = 0.041) potassium (p = 0.045), phosphorus (p = 0.001), and serum albumin levels (p = 0.047). Significant positive associations were found between protein and phosphorus intake (p = 0.012). Regression analysis showed a significant association between dietary phosphorus intake and hyperphosphatemia (p = 0.018). PD patients demonstrated inadequate protein intake compared with recommended renal nutrition guidelines. Increased dietary fiber intake was associated with higher potassium and phosphorus intake. Conclusion: Higher protein intake was associated with greater dietary fiber intake and patients dietary counselling should specifically emphasize on these two parameters. Constipation was the most commonly reported gastrointestinal symptom among our patients and the dietary counselling should also address this important clinical issue for a successful PD experience. Larger longitudinal studies are recommended to further evaluate the relationship between dietary intake, serum albumin, and nutritional outcomes among PD patients.